Models of neural networks II temporal aspects of coding and information processing in biological systems - Domany, E. (Eytan) 1947-; Hemmen, J.L. van (Jan Leonard) 1947-; Schulten, K. (Klaus) (Physics of neural networks, 1994)
Provides an in-depth analysis of both paradigms starting with an introduction to the ideas used in the subsequent chapters. In this book, one finds a discussion of salient features such as coherent oscillations and their detection, associative binding and segregation, Hebbian learning, and sensory computations in the visual and olfactory cortex.